Condition of sale of non-steroidal anti-inflammatory drugs authorized for marketing in colombia. strategy of rational use (2013)
The commercialization status (otc, under medical prescription, under special monitoring or for hospital use only) sets out the circumstances under which it may be publicized and marketed a drug. The otc does not involve consulting the health team, who do not participate in the selection of the drug, its dispensing or therapeutic monitoring. Present work through an observational, descriptive, cross-sectional study from the universe of Colombian drug approvals, identify and describe the variations in the condition of sale of non-steroidal anti-inflammatory drugs. For this pharmacological group, widely consumed in the country, dominated the modality "make and sell", the non-sterile solid dosage forms, the condition of sale under prescription and the enteric route of administration, likewise predominate as active substance diclofenac, followed by ibuprofen and piroxicam. Eight of the active ingredients of this pharmacological group have double condition of sale (otc and under medical prescription) achieving 70% of marketing authorization for nsaids in Colombia. It is evidenced a relationship between the amount of active substance per dosage unit and the commercialization status, a relationship that is not evident with respect to the indication.